Antibacterial Activity Studies on Some Bioactive Mannich Bases and Their Metal Ion Complexes - Santhi, P.R.; Poongothai, G. (Asian Journal of Chemistry, 2010)
In this study, bioactive Mannich base 5-pyrrolidinomethyl uracil (PMU), dimethylaminomethyl uracil (DMAMU) and (5-diethylaminomethyl)- 2-thio uracil (DEAMTU) and its metal ion complexes are synthesized by applying Mannich reaction using uracil/thiouracil as the active substrate secondary amine and formaldehyde. The structure of the complexes and ligands were characterized using spectral, elemental analysis and magnetic measurements. The Mannich bases were screened for their antibacterial activity against S. pyogenes and K. pneumoniae. The results showed that the metal chelates of the bioactive ligands have higher antibacterial activity than the free ligands.